Friction material and method for producing the same
Patent Information
- Application Number
- JP2021204865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2021-12-17
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0008】 本発明によれば、振動型アクチュエータの被駆動体を代表する摩擦材として、高湿度環境下においても高い摩擦力を発現し、耐食性、耐摩耗性に優れるとともに相手材の磨耗をより小さくできる部材を提供することができる。
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a friction material and a method for manufacturing the friction material. [Background technology]
[0002] A vibration actuator is known in which a vibrating body equipped with an electromechanical energy conversion element is brought into pressure contact with a driven body (contact body), exciting a predetermined vibration in the vibrating body, applying a frictional driving force from the vibrating body to the driven body, and moving the vibrating body and the driven body (contact body) relative to each other. The vibrating body is composed of a piezoelectric body and an elastic body bonded to the piezoelectric body. Vibrations generated by applying a voltage to the piezoelectric body are transmitted to the driven body via the elastic body. As mentioned above, the driving force of a vibration actuator depends on the frictional force acting between the elastic body and the driven body, so the driven body is required to function as a friction material. However, when left in a high-humidity environment, moisture is adsorbed on the surfaces of the elastic body and the driven body, resulting in a decrease in frictional force. To address this issue, Patent Document 1 proposes a method using a resin-impregnated stainless steel sintered body as the driven body.
[0003] In a typical vibration actuator, the elastic body has protrusions, the tips of which come into contact with the driven body. Because frictional forces act between the elastic body and the driven body, the surface of the driven body gradually wears away during operation. When deep wear marks form on the surface of the driven body, the damping performance of the vibration actuator deteriorates, making it difficult to use for long periods of time in applications requiring high damping accuracy. From these perspectives, the driven body requires high wear resistance. When using a material based on a stainless steel sintered body, it is considered effective to use a sintered material with extremely high hardness, as proposed in Patent Document 2.
[0004] However, the material described in Patent Document 2 has a structure in which carbides such as ZrC and NbC are dispersed and precipitated. Therefore, when used as a driven body in a vibration actuator, the presence of extremely hard carbide particles can cause wear of the elastic body that is the mating material. In addition, the presence of a different phase, carbide, in a pure stainless steel matrix makes it susceptible to corrosion such as intergranular corrosion, raising concerns about rust when used in a humid environment. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2017-225333 [Patent Document 2] Japanese Patent Application Laid-Open No. 2015-180763 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide a friction material that is representative of the driven body of a vibration actuator, which exhibits high frictional force even in a high humidity environment, has excellent corrosion resistance and wear resistance, and can reduce wear on the mating material. [Means for solving the problem]
[0007] The friction material that solves the above problems is A friction material comprising a stainless steel sintered material consisting of a martensite phase, an austenite phase, and a carbide phase, wherein the stainless steel sintered material contains carbon, In the stainless steel sintered material, The martensite ratio, which is the volume ratio of the martensite phase, is 44% or more, The carbon content, which is the weight ratio of the carbon, is 0.35 to 1.0 wt %, Contains 0.025% by weight or less of nitrogen, In the friction material, The ratio Ic / Im of the X-ray diffraction peak Im in the α' phase (110) plane to the peak Ic derived from FeC and CrC as the carbide phase is 0.08 or less. [Effects of the Invention]
[0008] According to the present invention, it is possible to provide a friction material that represents the driven body of a vibration actuator, which exhibits high frictional force even in a high humidity environment, has excellent corrosion resistance and wear resistance, and can reduce wear on the mating material. [Brief explanation of the drawings]
[0009] [Figure 1] 1 is a graph showing the results of X-ray diffraction of a friction material according to an embodiment of the present invention. [Figure 2] 1 is a schematic diagram showing the surface of a friction material according to an embodiment of the present invention; [Figure 3] 1 is a schematic diagram showing vibration-type actuators in examples of the present invention and comparative examples; FIG. [Figure 4] FIG. 1 is a schematic diagram showing a friction force evaluation device in examples and comparative examples of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0010] This embodiment is a friction material made of a porous, carbon-containing stainless steel sintered material. The stainless steel sintered material is composed of a martensite phase, an austenite phase, and a carbide phase. Specifically, the volume ratio of the martensite phase is 44% or more, the material contains 0.35 to 1.0 wt. % carbon, and 0.025 wt. % or less nitrogen. Furthermore, the friction material is characterized in that the ratio Ic / Im of the X-ray diffraction peak Im in the α'-phase (110) plane to the peak Ic derived from FeC and CrC is 0.08 or less. It is even better if the above-mentioned Ic / Im value is 0.06 or less. The carbon content, which is the weight ratio of carbon in the stainless steel sintered material, is preferably 0.4 to 0.8 wt. There are no limitations on the hardness of the friction material, but from the perspective of durability, a Vickers hardness of 800 or more is preferable. A friction material may be configured in which the half-width of the X-ray diffraction peak in the α'-phase (110) plane is 0.7 or more. The detection position of the X-ray diffraction peak in the α' phase (110) plane can be configured to be in the range of 44.1 to 44.5 in 2θ. The surface porosity of the sintered material is preferably 1% to 40%, and more preferably 2% to 20%. The friction material is made of a stainless steel sintered material and a resin impregnated into the pores contained in the stainless steel sintered material.
[0011] The friction material of this embodiment can be suitably used in a vibration actuator. Specifically, the vibration actuator has a vibrating body having an elastic body and an electromechanical energy conversion element, and a contact body that contacts the elastic body. The vibration of the vibrating body causes relative movement between the vibrating body and the contact body. It is possible to provide a vibration actuator using the above-mentioned friction material for at least one of the contact body and the vibrating body.
[0012] The method for producing a sintered material includes a step of mixing a stainless steel raw material powder and a carbon raw material powder to obtain a mixed powder, a step of pressurizing the mixed powder in a mold and then firing and quenching the resulting molded body, and a sub-zero treatment step performed after the firing step. This method for producing a sintered material is characterized in that the sub-zero treatment step is the final step.
[0013] The present invention will be described in detail below with reference to the drawings.
[0014] First, the raw materials for the sintered body will be described. Since the friction material of the present invention is intended to be used in a wet environment, stainless steel powder containing 10.5 wt% or more of Cr is used as the raw material. Furthermore, carbon powder is mixed to increase the hardness of the sintered body from the viewpoint of improving the wear resistance of the friction material. The mixed powder of stainless steel raw material powder and carbon raw material powder is used as the raw material for sintering. The amount of carbon mixed is preferably adjusted to be in the range of 0.35 wt% to 1.0 wt% in the resulting sintered body. This is because if the amount is less than 0.35 wt%, the amount of carbon dissolved in the martensite phase is insufficient, resulting in a decrease in hardness. If the amount is more than 1.0 wt%, the amount of retained austenite increases significantly, resulting in a similar decrease in hardness. More preferably, carbon is mixed to be in the range of 0.4 to 0.8 wt%. During the sintering process described below, some of the carbon powder contained in the raw materials is oxidized and desorbed, and the remaining carbon dissolves in the stainless steel to form martensite and austenite structures. Because it is difficult to completely suppress this desorption phenomenon, the amount of carbon mixed must be selected taking into account the amount of desorption depending on the sintering environment.
[0015] Next, we will explain the process for producing sintered bodies. A mold of the desired shape is prepared for the application, and the raw material powder is filled into the mold and pressed to produce a compact. The resulting compact is then sintered at a specified temperature and time, followed by cooling to produce a sintered body. During sintering, it is desirable to prepare a sintering environment with as low an oxygen concentration as possible to prevent the raw carbon powder from being burned away by oxidation. The resulting sintered body must be rapidly cooled after sintering to form the martensite phase. If rapid cooling is difficult, a quenching process can be added separately from the sintering process. However, in this case, carbides are likely to form, so it is preferable not to perform an additional heat treatment. The sintered body of the present invention is then completed by further sub-zero treatment of the intermediate sintered body obtained in this way. Sub-zero treatment can be performed using conventional methods, including cooling to below 0°C. Cooling methods that can be used include dry ice, carbon dioxide, and liquid nitrogen. To further increase hardness after treatment, a treatment temperature of -70°C or below is preferred. After sub-zero treatment, cracks may occur depending on the material and shape. If necessary, the sintered body may be placed in water or hot water for stress relief. In the present invention, the process of cooling to below 0°C and then immersing in water or hot water is referred to as the sub-zero treatment process. Although sub-zero treatment is an effective means for obtaining the material structure described below, it is not necessarily required if the desired structure is obtained at the stage of the intermediate sintered body.
[0016] Next, we will explain the characteristics of the material structure, etc., of the obtained sintered body. Rapid cooling after sintering results in a structure composed of a martensite phase, an austenite phase, and a trace amount of a carbide phase. As mentioned above, the carbon content is in the range of 0.35 wt% to 1.0 wt%, more preferably 0.4 to 0.8 wt%. While nitrogen improves hardness, it also has the problem of deteriorating corrosion resistance. Therefore, in the present invention, surface nitriding or other treatments are not performed and essentially no nitrogen is contained. Generally, in the environment in which stainless steel materials are manufactured, the inclusion of nitrogen from the air is unavoidable, so a content of 0.025 wt% or less is acceptable. The proportion of the martensite phase relative to the total volume can be evaluated using a magnetic measurement method such as a ferrite meter. In the present invention, the martensite phase must account for 44% or more. The proportion of the carbide phase can be evaluated by X-ray diffraction. Figure 1 shows the X-ray diffraction results of a friction material according to one embodiment of the present invention. The ratio Ic / Im of the peak Im of the α'(110) plane derived from martensite in Fig. 1 to the peak Ic derived from FeC or CrC detected in the 2θ range of 42.3 to 42.8 shown in Fig. 1 must be 0.08 or less. Since a smaller ratio of the carbide phase is desirable, it is more preferable that the ratio be 0.06 or less.
[0017] Finally, we will explain the post-processing steps for producing friction materials using the resulting stainless steel sintered compact. As described in Patent Document 1, resin impregnation can achieve higher frictional force in high-humidity environments, so it is desirable to impregnate the stainless steel sintered compact with resin. Impregnation can be performed using a standard vacuum impregnation process. One or more sintered compacts are placed in a vacuum chamber, which is then evacuated to below atmospheric pressure to remove air and absorbed moisture from the pores of the sintered compact. The impregnating resin is then introduced into the chamber. Various resins, such as acrylic, epoxy, silicone, phenolic, and polyester, are used as the impregnating resin. The components are appropriately adjusted to achieve low viscosity at room temperature for easy impregnation. To promote deeper impregnation, the chamber is pressurized above atmospheric pressure, then opened. The surface resin is removed by centrifugation or wiping, and the impregnated resin is then cured by heating. The heat treatment is performed using an appropriate method depending on the resin material selected; however, a simple method such as immersion in water at 80°C or higher can be used. While the use of a vacuum chamber allows for greater resin penetration to the interior, the impregnation method in the present invention is not limited to the above. For example, a suitable amount of impregnating resin material may be applied to the friction surface, then heated to reduce viscosity and allowed to penetrate by gravity. Furthermore, when used in applications requiring high braking performance, such as the driven body of a vibration actuator, polishing can be performed to reduce the surface roughness of the sliding surface. Examples of polishing methods include polishing with fixed abrasive grains, polishing with loose abrasive grains, and barrel polishing. However, care must be taken when using polishing abrasive grains that are too large, as this can leave large periodic polishing marks on the surface, crushing the pores created by sintering and preventing the impregnating resin from being exposed to the surface, thereby preventing the full effect of the present invention. If reducing surface roughness is not necessary for a particular application, post-processing is not necessarily required.
[0018] Figure 2 shows a schematic diagram of the surface of a friction member according to one embodiment of the present invention. The friction material 1, finally obtained after post-processing, has a morphology in which gaps formed when stainless steel raw material particles 2 bond together remain as pores 3. As described in Patent Document 1, in high-humidity environments, moisture adsorbed to the surface of the friction material exists as a water film, which acts as a lubricating layer and reduces friction. In contrast, the pores 3 act as a site for repelling the water film adsorbed on the surface, allowing high frictional force to be maintained even in high-humidity environments. Furthermore, as the distance around the actual contact area where frictional force is generated by the frictional sliding of two materials decreases, a process known as "break-in," it is thought that the water film becomes more likely to contribute to friction reduction. By adding a resin impregnation process, the resin impregnated in the pores transfers to the sliding surface during the sliding process, suppressing the progression of this "break-in," and therefore, it is thought that high frictional force can be obtained even in high-humidity environments. From these perspectives, the porosity of the friction material surface, which is a factor affecting frictional force under high humidity, needs to be controlled. To achieve sufficient effectiveness, the surface porosity must be 1% or more, and from the perspective of base material strength and wear resistance, it must be 40% or less. A surface porosity of 2% to 20% is preferable to achieve higher friction in high-humidity environments and higher wear resistance as a base material. Factors that control the porosity of the resulting sintered body during the sintering process include the particle size of the raw material powder, the pressure during molding, the sintering temperature, and the time. However, since these factors are greatly influenced by the type of material and the shape to be produced, appropriate conditions must be determined experimentally. Surface porosity can be measured by taking an observation image of the surface and quantifying the area ratio of pores on the surface using image processing software. [Example]
[0019] Next, the effects of the present invention will be demonstrated based on examples and comparative examples. The examples and comparative examples shown below illustrate application to the driven body (contact body) of a vibration actuator, but a configuration using a friction material may be adopted for at least one of the contact body and the vibrating body. Furthermore, the present invention is not limited to these examples and can be applied to other friction materials.
[0020] The stainless steel raw powders used were SUS410L (JIS standard: C 0.03 wt% or less, Cr 11.5-13.5 wt% or less, Si 0.5 wt% or less, Mn 1 wt% or less, P 0.04 wt% or less, S 0.03 wt% or less, balance Fe) and SUS434 (JIS standard: C 0.12 wt% or less, Cr 16.0-18.0 wt% or less, Mo 0.75-1.25 wt% or less, Si 1 wt% or less, Mn 1 wt% or less, P 0.04 wt% or less, S 0.03 wt% or less, balance Fe). These stainless steel powders were mixed with carbon powder at a total content of 0.4-1.2 wt% to obtain raw powder for compaction. This raw powder was filled into a 40-m long, 5-mm wide mold and compacted to a thickness of 1.5 mm under a load of 9000 kgf. The resulting compact was sintered at 1000°C to 1150°C for 30 minutes and then rapidly cooled to produce a sintered body. Some examples and comparative examples were then immersed in liquid nitrogen for 30 minutes as a sub-zero treatment, followed by immersion in room-temperature water for 10 minutes. Among the examples and comparative examples that did not undergo sub-zero treatment, some examples and comparative examples were subjected to a heat treatment for quenching, in which the sintered body was heated at 1000°C to 1150°C for 20 minutes and rapidly cooled. Furthermore, some of the examples and comparative examples that underwent such heat treatment were immersed in liquid nitrogen for 30 minutes as a sub-zero treatment. To confirm the effect of using sintered material in improving frictional force in a humid environment, Comparative Example 19 was prepared by pressing SUS420J2 ingot material into the same shape as the above examples (length: 40 mm, width: 5 mm, thickness: 1.5 mm), followed by quenching and nitriding. Table 1 shows the composition (wt%) and manufacturing process for Examples 1 to 11 and Comparative Examples 1 to 19. C (carbon content ratio) in Table 1 indicates the result of measuring the carbon content ratio contained in the sintered body produced by the combustion infrared absorption method.
[0021] Table 2 shows the various evaluation results for the sintered bodies obtained in Examples 1 to 11 and Comparative Examples 1 to 19. The evaluation methods for each evaluation item are described below. The open porosity of the sintered bodies was measured using the Archimedes method specified in JIS (JIS 1634:1998, "Method for Measuring Density and Open Porosity of Sintered Fine Ceramics"). The martensite ratio was measured by magnetic induction spectroscopy using a Fisher Instruments FISCHERSCOPE. Note that the measured values indicate the volume fraction of martensite components in the total volume, including pores. Therefore, they must be converted to a martensite ratio based on the volume of the sintered material itself, excluding the total porosity calculated from the theoretical density and bulk density. For example, if the measured value using magnetic induction spectroscopy is 40% and the total porosity of the sintered body is 10%, the martensite ratio should be calculated based on 90% excluding pores, i.e., 40 / 90 = 44.4%. The martensite ratio values listed in Table 2 are values calculated as described above. X-ray diffraction measurements were performed using a Rigaku Ultima 4 X-ray diffractometer. The X-ray diffraction measurements were performed using a Cu target at 40 kV and 40 mA output over a 2θ range of 35 to 60 degrees. The peak intensity Im of the α'(110) plane and the peak intensity Ic of FeC or CrC detected in the 2θ range of 42.3 to 42.8 were extracted from the obtained spectra, and the Ic / Im ratio was calculated. These peak intensities were calculated by subtracting the background intensity obtained from the non-detected region. The half-width and peak intensity detection position of the α'(110) plane peak were also calculated in terms of 2θ. Hardness measurements were performed using a Shimadzu HMV-2 Micro Vickers Hardness Tester. The measurement point was a pore-free area on the surface of the sintered body, and a pressing load of 0.98 N was applied.
[0022] Before the durability test and friction force evaluation, the specimens were polished to prepare the test components. Polishing was performed for 3 minutes using a #1200 grit SiC abrasive polishing sheet, followed by 3 minutes using a #4000 grit SiC abrasive polishing sheet. After polishing, the surface porosity was evaluated by surface observation and image analysis. The polished surface was photographed using an optical microscope at 200x magnification, and the resulting image data was binarized using image processing software. The area ratio of pores was calculated from the processed image. Ten locations on the friction surface were similarly measured, and the average values are shown in Table 2. The surface porosity of the polished surface was lower than the open porosity measured by the Archimedes method. This is presumably due to the plastic flow that occurs on the surface during polishing, which partially collapses the open pores.
[0023] Durability tests were conducted using the vibration actuator configuration shown in FIG. 3. The sintered bodies produced in Examples 1 to 11 and Comparative Examples 1 to 18 and the pressed member of Comparative Example 19 were used as the driven body 4 (contact body). The vibrating body 5 consisted of a substantially rectangular, flat-plate-shaped elastic body 5a serving as a base material and a substantially flat-plate-shaped piezoelectric element 5b bonded to one side of the elastic body 5a with an adhesive. The elastic body 5a had two protrusions 5c on the side opposite the side bonded to the piezoelectric element 5b (electromechanical energy conversion element), and the tips of the protrusions 5c contacted the driven body 4. The driven body 4 was in pressurized contact with the vibrating body 5 by a pressure means (not shown). By applying a voltage to the piezoelectric element 5b so as to generate an elliptical motion in the protrusions 5c, the driven body 4 and the vibrating body 5 could be moved relative to each other in the driving direction indicated by the arrow in FIG. 3. In this configuration, the driven body was reciprocated 100,000 times, and the wear state of the driven body surface was observed to evaluate durability. Considering the relationship between wear mark depth and braking performance, the criteria for judgment were as follows: ◎ if the maximum wear depth in the wear mark is 1 μm or less, ◯ if it is between 1 μm and 3 μm, and × if it is 3 μm or more.
[0024] Frictional force was evaluated using a Rhesca friction and wear tester, as shown in Figure 4. A sintered piece 8, fixed with screws, was placed on a movable stage 7. A pin 10 was placed in contact with the sintered piece 8 while a weight 9 was applied. The stage was then moved back and forth over a 10 mm range, and the frictional force was measured using a load sensor 11. A 2 mm diameter round bar made of SUS420J2 was used as the pin. The angle of the arm 12 was adjusted using a level to ensure it was horizontal before contact. The weight used was 150 g. First, a run-in sliding test was performed under the above conditions, with a travel speed of 20 mm / s and 5,000 reciprocating strokes. Then, the frictional force was measured in a dry state at a travel speed of 1 mm / s. The frictional force measured over a 10 mm range was averaged from 2 mm to 8 mm from the starting position, where the measured values were relatively stable. The coefficient of friction was calculated based on this average value. The sintered material and pin material were then left in a constant temperature and humidity chamber at 60°C and 90% for 20 hours, and immediately after being removed from the chamber, the pin material and sintered material were placed back in place, and the friction force was measured and the friction coefficient was calculated under the same conditions as when they were dried. The criteria for judging the friction force measurement results were as follows: if the friction coefficient after leaving in the constant temperature and humidity chamber at 60°C and 90% for 20 hours was 0.4 or higher, it was marked as ◎; if it was 0.3 or higher and less than 0.4, it was marked as ○; and if it was less than 0.3, it was marked as ×. The friction coefficient after leaving in the constant temperature and humidity chamber at 60°C and 90% was evaluated based on the average of three repeated measurements, taking into account measurement variability.
[0025] [Table 1]
[0026] [Table 2]
[0027] Comparative Example 19, which underwent nitriding treatment, was confirmed to have a nitrogen content exceeding 0.025 wt%. On the other hand, Examples and Comparative Examples other than Comparative Example 19 had a nitrogen content of 0.025 wt% or less. From the results shown in Table 2, it was found that the sintered bodies obtained in Examples 1 to 11, which had a martensite ratio of 44% or more and an Ic / Im value of 0.08 or less, had high hardness and achieved better results in durability tests than Comparative Examples 1 to 19. Among these, Examples 1 to 8, which had an Ic / Im of 0.06 or less and a carbon ratio in the range of 0.4 to 0.8 wt%, were found to have even higher hardness and superior durability. The Vickers hardness of the friction materials listed in the Examples was 800 or more. As shown in the table, specific Vickers hardness values ranged from 801 to 915.
[0028] On the other hand, in Comparative Example 1, although the martensite ratio was 44% or more, the Ic / Im value exceeded 0.08, and durability was poor. In Comparative Example 3, although the Ic / Im value was 0.08 or less, the martensite ratio was below 44%, and durability was also poor. Furthermore, compared with Comparative Example 19, good friction characteristics were obtained in all Examples, and it was confirmed that by using a sintered body, high friction force can be obtained even at high humidity.
[0029] Next, we will show examples in which a resin impregnation process was added to confirm the effects of resin impregnation. Examples 12 to 16 describe resin impregnation of the sintered bodies produced in Examples 1, 3, 6, 8, and 9. A polyester resin was selected as the impregnating agent. The sintered bodies were placed in a metal mesh basket and placed in a vacuum chamber. The lid was then closed and the chamber was depressurized to a pressure of 1 kPa or less. After depressurization, an amount of impregnating agent sufficient to fully immerse the metal mesh basket was added through a pipe connected to the chamber. The chamber was then pressurized. When the pressure rose to 0.5 MPa, the chamber was left for approximately 10 minutes. The chamber was then opened to the atmosphere, the sintered bodies were removed, their surfaces were wiped with a cloth, and the bodies were immersed in 80°C water for 20 minutes, then removed and dried. In this way, the resin-impregnated sintered materials used in Examples 12 to 16 were obtained. Table 3 shows the ingredients and manufacturing process of Examples 12 to 16, and Table 4 shows their evaluation results.
[0030] [Table 3]
[0031] [Table 4]
[0032] The results shown in Table 4 confirm that the friction characteristics in a humid environment are improved by impregnating the pores of the sintered body with resin. [Explanation of symbols]
[0033] 1 Friction material 2. Stainless steel particles 3 Stomata 4 Driven body (friction material) 5. Vibration body 5a Elastic body 5b Piezoelectric element 5c protrusion 6 Friction force measuring device 7 Movable stage 8 Friction material 9 weights 10 Pin material 11 Load sensor 12 Arm
Claims
1. A friction material comprising a stainless steel sintered material having a martensite phase, an austenite phase, and a carbide phase, the stainless steel sintered material containing carbon, In the stainless steel sintered material, the martensite ratio, which is the volume ratio of the martensite phase, is 44% or more, In the stainless steel sintered material, the carbon content ratio, which is the weight ratio of the carbon, is 0.35% by weight or more and 1.0% by weight or less, The stainless steel sintered body contains 0.025% by weight or less of nitrogen, A friction material characterized in that a ratio Ic / Im of an X-ray diffraction peak intensity Im in the α' phase (110) plane of the friction material to a peak intensity Ic derived from FeC or CrC contained in the carbide phase is 0.08 or less.
2. 2. The friction material according to claim 1, wherein the value of Ic / Im is 0.06 or less.
3. 3. The friction material according to claim 1, wherein the carbon content is 0.4% by weight or more and 0.8% by weight or less.
4. 4. The friction material according to claim 1, wherein the friction material has a Vickers hardness of 800 or more.
5. 5. The friction material according to claim 1, wherein the half-width of an X-ray diffraction peak measured at 2θ in the α' phase (110) plane is 0.7° or more.
6. 6. The friction material according to claim 1, wherein a detection position of an X-ray diffraction peak measured at 2θ on the α' phase (110) plane is within a range of 44.1° or more and 44.5° or less.
7. 7. The friction material according to claim 1, wherein the stainless steel sintered material has pores, and a surface porosity, which is the area ratio of the pores on the surface of the stainless steel sintered material, is 1% or more and 40% or less.
8. 8. The friction material according to claim 7, wherein the surface porosity is 2% or more and 20% or less.
9. A friction material as described in any one of claims 1 to 8, characterized in that the stainless steel sintered material has pores, and the friction material comprises the stainless steel sintered material and a resin impregnated in the pores.
10. A vibration actuator comprising a vibrator having an elastic body and an electromechanical energy conversion element, and a contact body in contact with the elastic body, the vibrator vibrating causes the vibrator and the contact body to move relative to each other, A vibration actuator using the friction material according to claim 1 for at least one of the contact body and the vibrating body.
11. A method for producing a stainless steel sintered material, comprising: a step of mixing stainless steel raw material powder and carbon raw material powder to obtain a mixed powder; a step of pressurizing the mixed powder in a die and then firing and rapidly cooling the resulting molded body; and a sub-zero treatment step carried out following the firing step, with the sub-zero treatment step being the final step in the method for producing a stainless steel sintered material.
12. The method for producing stainless steel sintered material according to claim 11, characterized in that in the step of obtaining the mixed powder, the amount of the mixture is such that the carbon content in the stainless steel sintered material after sintering is 0.4% by weight or more and 0.8% by weight or less.
13. 13. The method for producing a stainless steel sintered material according to claim 11, wherein the treatment temperature in the sub-zero treatment is minus 70° C. or lower.
14. A method for producing a friction material, comprising the steps of: carrying out the method for producing a sintered material according to any one of claims 11 to 13; and further carrying out a step of impregnating the obtained sintered material with a resin to obtain a friction material.
15. The method for producing a friction material according to claim 14, further comprising a step of polishing the sintered material.
